A Rh-catalyzed three-component reaction for the diastereoselective synthesis of pyrazolone derivatives with contiguous quaternary stereocenters. Issue 18 (24th April 2020) - Ao, Chaoqun; Huang, Jingjing; Xu, Xinfang; Jia, Shikun; Kang, Zhenghui; Hu, Wenhao
Abstract : Efficient approach for the facile construction of polyfunctionalized pyrazolone derivatives bearing two contiguous quaternary stereocenters in good yields with high regioselectivities and excellent diastereoselectivities. Abstract : A diastereoselective three-component reaction of diazo compounds with alcohols and pyrazolinone ketimines by utilizing rhodium(ii ) catalysis via interception of transient oxonium ylides is reported. The reaction provides an efficient approach for the facile construction of polyfunctionalized pyrazolone derivatives bearing two contiguous quaternary stereocenters in good yields with high regioselectivities and excellent diastereoselectivities.